An efficient strategy to boost photoelectrochemical water oxidation of g-C3N4 films modified with NiO as cocatalyst - Lingling Bi; Jiahao Zhan; Wenhao Zhang; Zhenzhou Wu; Weichuan Xu; Xiaobo Liang; Lijing Zhang; Bin Yan; Chunyi Xu (Scientific Reports)
Abstract The successful synthesis of carbon nitride films plays a crucial role in photoelectrochemical (PEC) water oxidation reactions. However, a significant technical challenge is that the contact between the g-C3N4 layer and the fluorine-doped tin oxide (FTO) substrate is suboptimal, as well as the recombination of photogenerated electrons and holes is grievous, directly affecting the effective charge transport and the overall photocatalytic efficiency. Herein, we fabricated a g-C3N4 thin photoanode through simple chemical vapor deposition, NiO cocatalyst was modified on the surface of g-C3N4 thin photoanode via electro-deposition and followed by calcination, aiming at improving the transfer of photogenerated charge carriers. As expected, the recombination of photogenerated electrons and holes is effectively suppressed the g-C3N4 thin photoanode after introducing NiO cocatalyst. Moreover, the superior electrical conductivity of NiO reduces charge transport resistance and allows photogenerated holes to be rapid injected into the electrolyte to participate in the water oxidation reaction. As such, the NiO-60s (the deposition time of NiO is 60 s) photoanode exhibits a higher photocurrent density and much negative onset potential than g-C3N4. which is of great benefit to designing effective g-C3N4 based photoanode for PEC water oxidation reaction.